The spectrophotometric determination of cisplatin in urine, using o-phenylenediamine as derivatizing agent - (:unkn) unknown (MARCEL DEKKER INC, 2001)
A visible spectrophotometric method has been developed fur determination of the antitumour agent cis-diammindichloroplatinum (II) in urine. The method is based on the measurement of the absorbance of the reaction product of the drug and o-phenylenediamine. Optimum conditions of the reaction were established. The product was obtained at pH 6.2; in 30 min at 90 degreesC, giving a maximum absorbance at 705 nm, which is far beyond the wavelengths of the absorption of cisplatin itself, o-phenylenediamine, and the biomolecules in urine. The chloride ion interference and the other possible interferences originated from the urine matrix were overcome by using the standard addition method and also the high concentration of the reactant. The drug could be detected and determined without any interference. The reaction product was stable in urine for 5 days at ambient temperature. The standard addition curve was linear in the concentration range of 0.42-3.16 mug/ml in respect to the final concentration of cisplatin. The detection limit of cisplatin in spiked urine samples was 8.40 mug/ml.
Keywords: visible spectrophotometer; cis-diammindichloroplatinum (II); cisplatin (CDDP); o-phenylenediamine (OPDA); determination; PERFORMANCE LIQUID-CHROMATOGRAPHY; CIS-DICHLORODIAMMINEPLATINUM(II); PLATINUM; PLASMA